2009
DOI: 10.1038/oby.2009.61
|View full text |Cite
|
Sign up to set email alerts
|

Rise in Extracellular Fluid Volume During High Sodium Depends on BMI in Healthy Men

Abstract: A high sodium (HS) intake is associated to increased cardiovascular and renal risk, especially in overweight subjects. We hypothesized that abnormal sodium and fluid handling is involved, independent of hypertension or insulin resistance. Therefore, we studied the relation between BMI and sodium‐induced changes in extracellular fluid volume (ECFV; distribution volume of 125I‐iothalamate) in 78 healthy men, not selected for BMI. A total of 78 subjects with a median BMI of 22.5 (range: 19.2–33.9 kg/m2) were stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 30 publications
4
18
0
Order By: Relevance
“…Brochner-Mortensen et al [5] matched obese and non-obese patients for height and age and found higher ECV in the obese, while Visser et al [20] recorded a positive correlation between BMI and the increase in ECV in response to a high sodium diet. One might expect these results, however, as they ignore the contribution to BMI of lean tissues and the fact that BMI bears a strong positive correlation with BSA (fig.…”
Section: Discussionmentioning
confidence: 99%
“…Brochner-Mortensen et al [5] matched obese and non-obese patients for height and age and found higher ECV in the obese, while Visser et al [20] recorded a positive correlation between BMI and the increase in ECV in response to a high sodium diet. One might expect these results, however, as they ignore the contribution to BMI of lean tissues and the fact that BMI bears a strong positive correlation with BSA (fig.…”
Section: Discussionmentioning
confidence: 99%
“…We rather think that this overestimation of mGFR results from an exaggerated correction of the distribution volume of creatinine when indexing with BSA. At this point, we remind readers that some authors have suggested that GFR should be indexed against extracellular volume rather than BSA, and it has actually been shown that a high sodium intake increased GFR but not GFR indexed to extracellular volume [53][54][55]. Moreover, it is interesting to note that the percentage of patients (including in non-CKD obese subjects) with indexed mGFR defining hyperfiltration was extremely low in our study, whereas hyperfiltration is a well-described functional and histological entity in obese subjects [14,47,56,57].…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16][17] To account for such bias, height normalization has been recommended, 14 as well as normalization to extracellular volume. 18,19 However, there is no validated gold standard. Unfortunately, data on extracellular volume were available in only a relatively small subset of persons in this study.…”
Section: Discussionmentioning
confidence: 99%